2021
DOI: 10.3389/fneur.2021.613027
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Unruptured Intracranial Aneurysms Do Not Impact Outcome in Patients With Acute Cerebral Infarction

Abstract: Background: This study was to examine the patients with acute cerebral infarction (ACI) treated at a single center over 9 years and who underwent Unruptured intracranial aneurysm (UIA) screening by three-dimensional time-of-flight magnetic resonance angiography (3D-TOF-MRA), and to explore the factors associated with outcomes.Methods: The outcome was the modified Rankin scale (mRS) score at 90 days after stroke onset. The outcome was classified into a good outcome (mRS score of 0–2 points) and poor outcome (mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Several studies have reported incidental intracranial aneurysms in patients ( 17 19 ). Oh et al collected data from 314 patients with IS, and the prevalence of incidental intracranial aneurysms was 6.1%; the presence of incidental intracranial aneurysms in IS patients was more evident in female and older patients ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported incidental intracranial aneurysms in patients ( 17 19 ). Oh et al collected data from 314 patients with IS, and the prevalence of incidental intracranial aneurysms was 6.1%; the presence of incidental intracranial aneurysms in IS patients was more evident in female and older patients ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that IS patients presented with a higher prevalence of intracranial aneurysms than the general population, while IS patients who had intracranial aneurysms did not have an effect on functional outcomes ( 18 ). Wu et al retrospectively collected data from 4,033 patients with IS and found that 6.5% of patients presented with UIA, and incidental UIA was not associated with the prognosis of IS ( 19 ). However, the risk factors and predictive models for UIA in patients with IS remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] It is complicated with respiratory, circulatory, blood, and other system diseases or has a history of corresponding diseases in the past.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…The results show that [ 1 ]: The most significant and meaningful terms in biological process are metabolic process and RNA splicing, which describe a series of biological events ( Figure 5a-d ) [ 2 ]. As far as cell components are concerned, the most important enrichment and meaningful terms are intracellular parts and complexes, describing cell components ( Figure 6a-d ) [ 3 ]. As far as molecular function is concerned, the most important enrichment and meaningful term is the binding event, which indicates the function at the molecular level ( Figure 7a-d ).…”
Section: Go and Pathway Analysis Of Putative Target Genesmentioning
confidence: 99%
See 1 more Smart Citation